SPECIAL DAMPER FOR REDUCING VIBRATION OF FLOATING CRANE POWER PLANT - Anatoly A. Korotkiy; Valery E. Kasyanov; Elena V. Yegelskaya (Advanced Engineering Research)
The damper design for the high - power plants is presented. (The efficiency effect in reducing the vibration levels in th e operator’s compartment at his worksite is shown.)